A MATHEMATICAL MODEL FOR DETERMINING THE ORIGIN OF CONSUMER ELECTRICITY FROM RENEWABLE ENERGY SOURCES IN THE ENERGY SUPPLY SYSTEM - HUNKO, IRYNA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The research paper describes a method for estimating the part of a particular consumer's electricity consumption that is generated by renewable sources of energy. The basis of the method is a mathematical model that determines the components of electricity flows in the branches of the electric grid using the coefficients of current distribution in the branches of the circuit from RES nodes and nodal voltages. Determining the part of electricity that consumers are guaranteed to receive from renewable sources of energy creates conditions to encourage generating companies and consumers to increase the use of renewable energy and promote the development of the green energy market. Also, confirmation of electricity from renewable sources allows businesses to produce products with green labeling, which makes them more competitive in European markets and eliminates additional taxation.The research presents the results of computer and mathematical modeling of a fragment of the power system, which operates 2 photovoltaic stations and a local electric energy system. The power generation capacity of the photovoltaic stations is 15 MW each. The power consumption of the local electric power system is 25 MW. The results of the calculations show that the local electric energy system consumed 12.24 MW from renewable energy sources, while the rest was consumed by other consumers of the grid. The offered method also allows to estimate power losses in the power grid caused by flows from renewable sources of energy. In the considered grid, the total power losses amount to 1.828 MW, including 1.1 MW from the transmission of power from RSE, which coincided with the results of the computer simulation performed in the Power Factory software package.
Keywords: guarantees of origin; renewable sources of energy; mathematical model; local electric energy system